Deficiency of β-arrestin2 exacerbates inflammatory arthritis by facilitating plasma cell formation - Zhou Wei-jie; Wang Dan-dan; Tao Juan; Tai Yu; Zhou Zheng-wei; Wang Zhen; Guo Pai-pai; Sun Wu-yi; Chen Jing-yu; Wu Hua-xun; Yan Shang-xue; Zhang Ling-ling; et al. (Acta Pharmacologica Sinica, 2021)
β-arrestin2 (β-arr2) is, a key protein that mediates desensitization and internalization of G protein-coupled receptors and participates in inflammatory and immune responses. Deficiency of β-arr2 has been found to exacerbate collagen antibody-induced arthritis (CAIA) through unclear mechanisms. In this study we tried to elucidate the molecular mechanisms underlying β-arr2 depletion-induced exacerbation of CAIA. CAIA was induced in β-arr2−/− and wild-type (WT) mice by injection of collagen antibodies and LPS. The mice were sacrificed on d 13 after the injection, spleen, thymus and left ankle joints were collected for analysis. Arthritis index (AI) was evaluated every day or every 2 days. We showed that β-arr2−/− mice with CAIA had a further increase in the percentage of plasma cells in spleen as compared with WT mice with CAIA, which was in accordance with elevated serum IgG1 and IgG2A expression and aggravating clinical performances, pathologic changes in joints and spleen, joint effusion, and joint blood flow. Both LPS stimulation of isolated B lymphocytes in vitro and TNP-LPS challenge in vivo led to significantly higher plasma cell formation and antibodies production in β-arr2−/− mice as compared with WT mice. LPS treatment induced membrane distribution of toll-like receptor 4 (TLR4) on B lymphocytes, accordingly promoted the nuclear translocation of NF-κB and the transcription of Blimp1. Immunofluorescence analysis confirmed that more TLR4 colocalized with β-arr2 in B lymphocytes in response to LPS stimulation. Depletion of β-arr2 restrained TLR4 on B lymphocyte membrane after LPS treatment and further enhanced downstream NF-κB signaling leading to additional increment in plasma cell formation. In summary, β-arr2 depletion exacerbates CAIA and further increases plasma cell differentiation and antibody production through inhibiting TLR4 endocytosis and aggravating NF-κB signaling.